Publisher Correction: Coordinated targeting of cold and nicotinic receptors synergistically improves obesity and type 2 diabetes. Issue 1 (December 2018) - Clemmensen, Christoffer; Jall, Sigrid; Kleinert, Maximilian; Quarta, Carmelo; Gruber, Tim; Reber, Josefine; Sachs, Stephan; Fischer, Katrin; Feuchtinger, Annette; Karlas, Angelos; Simonds, Stephanie; Grandl, Gerald; et al.
In the original PDF version of this article, affiliation 1, 'Institute for Diabetes and Obesity, Helmholtz Diabetes Center (HDC), Helmholtz Zentrum Muenchen & German Center for Diabetes Research (DZD), Neuherberg, Germany', was incorrectly given as 'Institute of Diabetes and Regeneration Research, Helmholtz Zentrum Muenchen, German Research Center for Environmental Health (GmbH), Neuherberg, Germany '. This has now been corrected in the PDF version of the article; the HTML version was correct at the time of publication.